Pembaharuan Pendidikan Islam Konsep Pendidikan Tinggi Islam Menurut Pemikiran Fazlur Rahman - Aan Najib (FITK UIN Walisongo, 2015)
Fazlur Rahman idea of renewal Islamic college is lead to improvement of the current Islamic education. The final conclusion of this paper is (1).the formulation of thought the concept of Islamic higher education to be developed must be built on a solid paradigm spiritually, superior intellectually, and graceful morally with the Qur'an as a first reference and foremost. (2) offer a curriculum that are open to the studies of philosophy and social-science. (3) If the Islamic college in Indonesia is willing to follow the educational Fazlur Rahman thinking, motivation Indonesian Muslims to the development of science will be stronger, the dichotomy of science will be increasingly eroded.AbstrakGagasan Fazlur Rahman tentang pembaharuan pendidkan tinggi Islam sangat berhubungan dengan peningkatan pendidikan Islam masa kini. Kesimpulan akhir dari makalah ini adalah (1) formulasi pemikiran tentang konsep pemikiran mengenai pendidikan tinggi Islam yang akan dikembangkan harus dibangun di atas paradigma spiritual yang solid, unggul secara intelektual, dan anggun secara moral sesuai dengan Al-Qur'an sebagai rujukan pertama dan terutama. (2) kurikulum yang terbuka untuk studi filsafat dan ilmu sosial. (3) Jika perguruan tinggi Islam di Indonesia bersedia mengikuti pemikiran pendidikan Fazlur Rahman, maka keinginan umat Islam Indonesia untuk pengembangan ilmu pengetahuan akan lebih kuat, dikotomi ilmu akan semakin terkikis.